Regression Analysis to Determine the Influence of the Social Environment on Student Achievement in Islamic Religious Education. - Safitri Safitri; Dian Kusuma Wardani; Nanang Qosim; Mohammed Emier Azka (PALAPA, 2026)
Although the social environment has received relatively limited empirical attention in studies on student learning outcomes in Islamic Religious Education (IRE), it plays an important role in shaping academic success and learning behavior. This study aims to examine the effect of the social environment on students’ learning outcomes in IRE at SMPN 1 Tembelang. A quantitative approach with a survey design was employed, involving all students as participants through saturated sampling. Data were collected through questionnaires, direct observations, documentation, and students’ report card results. The data were analyzed using descriptive statistics and simple linear regression. The findings indicate that the social environment has a positive and statistically significant effect on students’ IRE learning outcomes, as shown by a significance value of 0.006, which is lower than the 0.05 significance level. These findings support the perspectives of social learning theory and ecological development theory, which emphasize the role of social interaction in facilitating the learning process. This study concludes that a supportive and conducive social environment plays an essential role in improving students’ learning achievement in IRE. The findings contribute to Islamic education literature by providing empirical evidence on the importance of social-environmental factors in student learning outcomes and imply that schools should strengthen social support systems to enhance students’ academic performance.